2020
DOI: 10.1051/e3sconf/202018902021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin on physical fatigue and oxidative damage in forced swimming mice

Abstract: The purpose of the present study was to investigate the effects of curcumin on physical fatigue and oxidative damage induced by forced swimming exercise in mice. The mice were divided into quiet group and exercise group, and then the above two groups were divided into control group and medication group. The medication group received curcumin (100 mg/kg), while the control group received physiological saline for 28 days. The exercise group performed swimming exercise for 4 weeks and then performed exhaustive ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Curcumin and curcumin analogues reduced the scopolamine-induced oxidative stress in the hippocampus of the mouse brain. Numerous studies have shown that curcumin considerably reduces oxidative stress and has significant antioxidant effects [ 39 , 70 ]. According to research, scopolamine induces oxidative stress in the brain tissue of mice by increasing lipid peroxidation and decreasing the activity of antioxidant enzymes [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin and curcumin analogues reduced the scopolamine-induced oxidative stress in the hippocampus of the mouse brain. Numerous studies have shown that curcumin considerably reduces oxidative stress and has significant antioxidant effects [ 39 , 70 ]. According to research, scopolamine induces oxidative stress in the brain tissue of mice by increasing lipid peroxidation and decreasing the activity of antioxidant enzymes [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The practices in the treatment of periodontitis, antiparasitic and anti-tumor therapy, showed that curcumin has achieved good therapeutic, indeed, with few side effects, and is easy to administrate [12][13][14]. In addition, modern pharmacology also proves that curcumin does have various biological activities [15,16] and possesses the characteristics of weak toxic and side effects [17,18], with a few research confirming its ability to mitigate exercise fatigue [19][20][21], but the mechanism behind this is still poorly understood. Because of the antioxidant and anti-inflammatory activity of curcumin, previous studies hypothesized that its anti-fatigue mechanism may be linked to glucose and lipid metabolism [10,22] and tissue protection [23].…”
Section: Introductionmentioning
confidence: 99%